Benfotiamine, a Lipid-Soluble Analog of Vitamin B1, Improves the Mitochondrial Biogenesis and Function in Blunt Snout Bream (Megalobrama amblycephala) Fed High-Carbohydrate Diets by Promoting the AMPK/PGC-1β/NRF-1 Axis - Xu, Chao; Liu, Wen-Bin; Zhang, Ding-Dong; Shi, Hua-Juan; Zhang, Li; Li, Xiang-Fei (Frontiers in Physiology, 2018)
This study evaluated the effects of benfotiamine on the growth performance and mitochondrial biogenesis and function in Megalobrama amblycephala fed high-carbohydrate (HC) diets. The fish (45.25 ± 0.34 g) were randomly fed six diets: the control diet (30% carbohydrate, C), the HC diet (43% carbohydrate), and the HC diet supplemented with different benfotiamine levels (0.7125 (HCB1), 1.425 (HCB2), 2.85 (HCB3), and 5.7 (HCB4) mg/kg) for 12 weeks. High-carbohydrate levels remarkably decreased the weight gain rate (WGR), specific growth rate (SGR), relative feed intake (RFI), feed conversion ratio (FCR), p-adenosine monophosphate (AMP)-activated protein kinase (AMPK)α/t-AMPKα ratio, peroxisome proliferator-activated receptor-γ coactivator-1β (PGC-1β) and nuclear respiratory factor-1 (NRF-1) protein expression, complexes I, III, and IV activities, and hepatic transcriptions of cytochrome b (CYT-b) and cytochrome c oxidase-2 (COX-2), whereas the opposite was true for plasma glucose, glycated serum protein, advanced glycation end product and insulin levels, tissue glycogen and lipid contents, hepatic adenosine triphosphate (ATP) and AMP contents and ATP/AMP ratio, complexes V activities, and the expressions of AMPKα-2, PGC-1β, NRF-1, mitochondrial transcription factor A (TFAM), mitofusin-1 (Mfn-1), optic atrophy-1 (Opa-1), dynamin-related protein-1 (Drp-1), fission-1 (Fis-1), mitochondrial fission factor (Mff), and ATP synthase-6 (ATP-6). As with benfotiamine supplementation, the HCB2 diet remarkably increased WGR, SGR, tissue glycogen and lipid contents, AMP content, p-AMPKα/t-AMPKα ratio, PGC-1β and NRF-1 levels, complexes I, III, IV, and V activities, and hepatic transcriptions of AMPKα-2, PGC-1β, NRF-1, TFAM, Mfn-1, Opa-1, CYT-b, COX-2, and ATP-6, while the opposite was true for the remaining indicators. Overall, 1.425 mg/kg benfotiamine improved the growth performance and mitochondrial biogenesis and function in fish fed HC diets by the activation of the AMPK/PGC-1β/NRF-1 axis and the upregulation of the activities and transcriptions of mitochondrial complexes as well as the enhancement of mitochondrial fusion coupled with the depression of mitochondrial fission.